2009
DOI: 10.1038/mt.2008.228
|View full text |Cite
|
Sign up to set email alerts
|

Phase Ib Trial of Mutant Herpes Simplex Virus G207 Inoculated Pre-and Post-tumor Resection for Recurrent GBM

Abstract: We have previously demonstrated safety of G207, a doubly mutated (deletion of both gamma(1)34.5 loci, insertional inactivation of U(L)39) herpes simplex virus (HSV) for patients stereotactically inoculated in enhancing portions of recurrent malignant gliomas. We have now determined safety of two inoculations of G207, before and after tumor resection. Inclusion criteria were histologically proven recurrent malignant glioma, Karnofsky score >or=70, and ability to resect the tumor without ventricular system breac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
288
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(296 citation statements)
references
References 34 publications
6
288
0
2
Order By: Relevance
“…2 As most tumor recurrences are within the initial tumor bed, direct injection of attenuated oncolytic viruses such as herpes simplex virus-1 (HSV-1) has been proposed as an adjuvant treatment and utilized in Phase I clinical trials for high-grade gliomas. [3][4][5][6][7] HSV-1 is a double-stranded DNA virus expressing its genes in a sequential cascade of immediate-early (a), early (b), and late (g) genes. 8 Immediate-early genes encode for viral transcriptional regulators.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 As most tumor recurrences are within the initial tumor bed, direct injection of attenuated oncolytic viruses such as herpes simplex virus-1 (HSV-1) has been proposed as an adjuvant treatment and utilized in Phase I clinical trials for high-grade gliomas. [3][4][5][6][7] HSV-1 is a double-stranded DNA virus expressing its genes in a sequential cascade of immediate-early (a), early (b), and late (g) genes. 8 Immediate-early genes encode for viral transcriptional regulators.…”
Section: Introductionmentioning
confidence: 99%
“…10 Phase I clinical trials in patients with glioma have been completed with neuro-attenuated HSV-1 deleted of g 1 34.5 that have demonstrated the safety and feasibility of this approach. [4][5][6] However in creating clinically safe, replication-competent viruses, the therapeutic trade-off is decreased viral replication to maintain safety that hampers anti-tumor efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 This was confirmed by early clinical trials in patients injected intratumorally (glioma) with oHSVs: sporadic shedding of HSV in saliva was noted, but this was shown to be wildtype virus as opposed to the injected oHSV. 11,12 Other studies have observed limited leakage of oHSV from injection sites up to 2 weeks post treatment, without other excreta containing viable oHSV. [13][14][15] Intra-arterial hepatic injection did not result in detectable environmental shedding either.…”
Section: Family Herpesviridae: Herpes Simplex Virus 1 (Hsv)mentioning
confidence: 99%
“…62 Attenuated HSVs have already been successfully used in Phase I/II trials for treatment of central nervous system (CNS) glioblastoma without apparent nonspecific toxic effects. 63,64 The efficacy and potency of peripheral opioid effects are generally enhanced when drugs are administered during active inflammatory conditions. [65][66][67][68][69] Development of opiate tolerance?…”
Section: Comparison Of Viral Vectors For Analgesic and Anti-inflammatmentioning
confidence: 99%
“…[79][80][81][82][83][84] Replication-deficient virus has been used safely without spread when injected directly into brain as treatment for glioblastoma. 63,64,84 Owing to the success of opioid gene therapy we have described in recent published studies for rats with pancreatitis, 20,21 continued efficacy and safety testing of HSV viral vector therapies for patient use is warranted.…”
Section: Testing Safety and Efficacy Issuesmentioning
confidence: 99%